Pengaruh Bahan Ajar Berbasis Self-Efficacy pada Pembelajaran Statistika SMP terhadap Kecemasan Matematika Siswa - Ahmad Dzulfikar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
Student`s self-efficacy in learning mathematics and its resources, such as student`s positive emotional conditions, have been impactful to create a pleasant mathematical learning and the reduction of student`s mathematics anxiety. This study investigated the differences between student`s mathematics anxiety before and after the implementation of mathematics teaching materials based on self-efficacy in statistical learning in mathematics classroom. This study was an experimental study with One Group Pretest-posttest Design. The population of the study was all eight grade students in one of the junior high schools in Pekalongan in the 2017/2018 academic year. The sample of the study involved 28 students taken by cluster sampling technique. After analyzing the data, this study found that mathematics teaching materials based on self-efficacy effectively helped reduce student`s mathematics anxiety, either when they learn in math class or when they face math tests, or both. Even so, the level of student`s anxiety when they face the math test was at a moderate level, both before and after the treatment, i.e. the implementation of mathematics teaching materials based on self-efficacy in the learning. Therefore, further research about the effect of this teaching materials on student`s mathematics anxiety when facing tests is still needed